Chronic comorbidities in children and adolescents with perinatally acquired HIV infection in sub-Saharan Africa in the era of antiretroviral therapy. (September 2020) - Frigati, Lisa J; Ameyan, Wole; Cotton, Mark F; Gregson, Celia L; Hoare, Jacqueline; Jao, Jennifer; Majonga, Edith D; Myer, Landon; Penazzato, Martina; Rukuni, Ruramayi; Rowland-Jones, Sarah; Zar, Heather J; et al.
Summary: Globally, 1·7 million children are living with HIV, of which 90% are in sub-Saharan Africa. The remarkable scale-up of combination antiretroviral therapy has resulted in increasing numbers of children with HIV surviving to adolescence. Unfortunately, in sub-Saharan Africa, HIV diagnosis is often delayed with children starting antiretroviral therapy late in childhood. There have been increasing reports from low-income settings of children with HIV who have multisystem chronic comorbidities despite antiretroviral therapy. Many of these chronic conditions show clinical phenotypes distinct from those in adults with HIV, and result in disability and reduced quality of life. In this Review, we discuss the spectrum and pathogenesis of comorbidities in children with HIV in sub-Saharan Africa. Prompt diagnosis and treatment of perinatally acquired HIV infection is a priority. Additionally, there is a need for increased awareness of the burden of chronic comorbidities. Diagnostic and therapeutic strategies need to be collectively developed if children with HIV are to achieve their full potential.